The efficiency of real-time ultrasonography to assess early pregnancy and fetal number in first trimester period for Awassi ewes - Laith Sofian Younis; Saad Akram Hatif (The Indian Veterinary Journal, 2024)
This article aims to predict the reliability of B-mode ultrasonography (ULR) for early pregnancy detection and determine gestational type in Awassi ewes. Two techniques were used through the first trimester, Transrectal (TRU) and Transabdominal (TAU) ultrasonography with frequencies of 6.5 MHz and 3.5-4.5 MHz, respectively. Thirty ewes were synchronized and exposed to five rams at estrus. The early gestation was detected by ULR scanning at different periods (15, 25, 35, and 50 days post mating). The findings indicated highly significant effect (P<0.01) of pregnancy stage on the Accuracy (Acc) of ULR for predicting pregnancy; the Sensitivity (Se), Specificity (Sp) and Acc was low (8%, 60% and 16.6%) at day 15, it began to rise at day 25 (68%, 80% and 70%) and at day 35 (92%, 80% and 90%) postmating, then it reached 100% at day 50. The correlation between fetal age and Gestational Sac Diameter (GSD) was higher (R² = 0.8809) between the period 21-35, and with Crown Ramp Length (CRL) (0.9852) during the period 30-50. The ultrasonography showed high efficiency to determine pregnancy type, it was significant (P<0.01) influenced by day of gestation; Se, Sp, PV+, PV- and Acc were high at day 30-35 and reached100% at day 50 of gestation. Lastly, the pregnancy phase may impact significantly on ultrasound prediction of pregnancy, fetal age, and number. Since the prediction rate of UTR technique reach to 100% at day 50, it can be use as a gold standard for pregnancy and litter size detection on day 50.